2021
DOI: 10.1002/pits.22499
|View full text |Cite
|
Sign up to set email alerts
|

A survey of newly enrolled school psychology trainees: Estimates of key role and function

Abstract: Examining school psychology trainees' perceptions regarding school psychologists' key role and function is important because inaccurate perceptions may lead to unmet professional expectations, reduced job satisfaction, and burnout. One hundred and eighty two first‐year school psychology graduate students enrolled in National Association of School Psychologists (NASP) approved and/or American Psychological Association accredited school psychology specialist and/or doctoral training programs were surveyed regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Areas covered under this domain consist of school-wide social-emotional programming, applied behavior analysis, behavioral coaching, and individual and group counseling. Even with the inclusion of counseling into the most recent NASP standards and practice model, school psychologists continue to spend over half of their time in assessment-related roles and only about 7% of their time providing individual and group counseling (Weiner et al, 2021 ). Interestingly, in instances where there is a low school psychologist to student ratio, school psychologists spend several hours per week providing individual and group counseling to students (Eklund et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Areas covered under this domain consist of school-wide social-emotional programming, applied behavior analysis, behavioral coaching, and individual and group counseling. Even with the inclusion of counseling into the most recent NASP standards and practice model, school psychologists continue to spend over half of their time in assessment-related roles and only about 7% of their time providing individual and group counseling (Weiner et al, 2021 ). Interestingly, in instances where there is a low school psychologist to student ratio, school psychologists spend several hours per week providing individual and group counseling to students (Eklund et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stinnett et al (2013) found that 25%-30% of a sample of undergraduate students were misinformed about the field of school psychology. Furthermore, incoming graduate students may also have misconceptions about the roles and responsibilities of school psychologists (Weiner et al, 2021). Because this informational mismatch can further lead to burnout when students begin to practice school psychology (Schilling & Randolph, 2021), accurate and thorough information is crucial in the recruitment of prospective school psychology graduate students.…”
mentioning
confidence: 99%
“…School psychology faculty must consider further opportunities to recruit students beyond assumed exposure to the profession. Better information is also needed as current school psychology graduate students believe there is a mismatch between their anticipated expectations of the field compared to the reality of a school psychologists' daily tasks (Weiner, 2018). This mismatch may be attributed to the misinformation undergraduate students are receiving in the roles of a school psychologist.…”
mentioning
confidence: 99%